Blockade of T-type calcium channels by 6-prenylnaringenin, a hop component, alleviates neuropathic and visceral pain in mice. (August 2018) - Sekiguchi, Fumiko; Fujita, Tomoyo; Deguchi, Takahiro; Yamaoka, Sakura; Tomochika, Ken; Tsubota, Maho; Ono, Sumire; Horaguchi, Yamato; Ichii, Maki; Ichikawa, Mio; Ueno, Yumiko; Koike, Nene; et al.
Abstract: Since Cav 3.2 T-type Ca 2+ channels (T-channels) expressed in the primary afferents and CNS contribute to intractable pain, we explored T-channel-blocking components in distinct herbal extracts using a whole-cell patch-clamp technique in HEK293 cells stably expressing Cav 3.2 or Cav 3.1, and purified and identified sophoraflavanone G (SG) as an active compound from SOPHORAE RADIX (SR). Interestingly, hop-derived SG analogues, (2 S )-6-prenylnaringenin (6-PNG) and (2 S )-8-PNG, but not naringenin, also blocked T-channels; IC50 (μM) of SG, (2 S )-6-PNG and (2 S )-8-PNG was 0.68–0.75 for Cav 3.2 and 0.99–1.41 for Cav 3.1. (2 S )-6-PNG and (2 S )-8-PNG, but not SG, exhibited reversible inhibition. The racemic (2 R/S )-6-PNG as well as (2 S )-6-PNG potently blocked Cav 3.2, but exhibited minor effect on high-voltage-activated Ca 2+ channels and voltage-gated Na + channels in differentiated NG108-15 cells. In mice, the mechanical allodynia following intraplantar (i.pl.) administration of an H2 S donor was abolished by oral or i.p. SR extract and by i.pl. SG, (2 S )-6-PNG or (2 S )-8-PNG, but not naringenin. Intraperitoneal (2 R/S )-6-PNG strongly suppressed visceral pain and spinal ERK phosphorylation following intracolonic administration of an H2 S donor in mice. (2 R/S )-6-PNG, administered i.pl. or i.p., suppressed the neuropathic allodynia induced by partial sciatic nerve ligation or oxaliplatin, an anti-cancer agent, in mice. (2 R/S )-6-PNG had little or no effect on open-field behavior, motor performance or cardiovascular function in mice, and on the contractility of isolated rat aorta. (2 R/S )-6-PNG, but not SG, was detectable in the brain after their i.p. administration in mice. Our data suggest that 6-PNG, a hop component, blocks T-channels, and alleviates neuropathic and visceral pain with little side effects. Graphical abstract: Image 1 Highlights: Cav 3.2 T-type Ca 2+ channels contribute to intractable pain. We identified sophoraflavanone G from SOPHORAE RADIX as a T-channel blocker. The analogues, 6- and 8-prenylnaringenin, derived from hops, also blocked T-channels. 6-Prenylnaringenin had the most preferable characteristics as a T-channel blocker. 6-Prenylnaringenin alleviated neuropathic and visceral pain with little side effects.